2010
DOI: 10.1007/s11864-010-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia: Traditional Therapies and Novel Molecular Mechanism-Based Approaches to Treatment

Abstract: Opinion statementThe complex syndrome of cancer cachexia (CC) that occurs in 50% to 80% cancer patients has been identified as an independent predictor of shorter survival and increased risk of treatment failure and toxicity, contributing to the mortality and morbidity in this population. CC is a pathological state including a symptom cluster of loss of muscle (skeletal and visceral) and fat, manifested in the cardinal feature of emaciation, weakness affecting functional status, impaired immune system, and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 37 publications
6
71
0
2
Order By: Relevance
“…These results showing the amelioration of pro-inflammatory markers, i.e., NF-κB p65, COX-2, and TGF-β 1 protein expressions, are in parallel with a recent report showing enhanced COX-2 protein expression due to NF-κB activation. 40) These results also confirm our previous work 18) that the suppression of inflammation by the modulation of NF-κB p65 and COX-2 is a critical factor contributing to an anti-diabetic action.…”
Section: )supporting
confidence: 89%
“…These results showing the amelioration of pro-inflammatory markers, i.e., NF-κB p65, COX-2, and TGF-β 1 protein expressions, are in parallel with a recent report showing enhanced COX-2 protein expression due to NF-κB activation. 40) These results also confirm our previous work 18) that the suppression of inflammation by the modulation of NF-κB p65 and COX-2 is a critical factor contributing to an anti-diabetic action.…”
Section: )supporting
confidence: 89%
“…15,16 Malnutrition has been documented globally among 30-80% of cancer patients. [17][18][19] The consequences of malnutrition may include an increased risk of morbidity, decreased response and tolerance to treatment, a decline in quality of life, higher health-care costs and reduced survival. [20][21][22] Reported dietary intake of advanced cancer patients suggests that their total calorie intake is 1610+686 kcal/d which is 4-53 kcal/kg body weight/d.…”
Section: Consequences Of Malnutritionmentioning
confidence: 99%
“…23 Kumar et al also documented a calorie deficit of approximately 250-400 kcal/d among weight losing cancer patients. 18 Anemia is commonly reported in advanced cancer patients, leading to altered energy homeostasis and reduction in physical activity. 24 Advanced cancer patients have deficiency of essential micronutrients like zinc, selenium, vitamin C and vitamin E, which support body's immune response.…”
Section: Consequences Of Malnutritionmentioning
confidence: 99%
“…Recent human studies have found that supplementation with long chain n-3 PUFA increases rates of protein synthesis and augments the muscle protein anabolic response, and may also attenuate acute muscle loss (cachexia) (236)(237)(238)(239)(240)(241) . One small observational study found a negative association with appendicular lean mass and saturated fat, and a comprehensive study of dietary fat composition and muscle mass found positive associations with the PUFA:SFA ratio and negative associations with saturated and trans fatty acids (15,81) .…”
Section: Dietary Fat Compositionmentioning
confidence: 99%